Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.21203/rs.3.rs-1806075/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Commercial civet farming practices and conservation impacts on wild civet populations in central Vietnam

Abstract: Demand for luxury wild meat and civet coffee has driven the establishment of civet farms in South-east Asia, including in Vietnam. However, little is known about the impacts of these farms on wild civet populations. In 2020, semi-structured interviews were used to explore the status and trade dynamics of 57 commercial civet farms in Lam Dong and Dak Lak provinces, Vietnam. Interviewees comprised civet farm owners as well as local government staff that were mandated to monitor these facilities. The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…More recent research, however, has challenged this analysis and identified flaws in the method of the original research [9,85]. Civet coffee collection methods are also widely falsified [86], and although consumers are led to believe civet coffee is produced through the collection of civet faeces by Indonesian farmers, the reality is the mass farming of caged civets to meet the demand of the global market [87]. Civet coffee's global market is currently increasing and is expected to reach US $11.75 billion by 2030 [77].…”
Section: Civet Coffeementioning
confidence: 99%
See 4 more Smart Citations
“…More recent research, however, has challenged this analysis and identified flaws in the method of the original research [9,85]. Civet coffee collection methods are also widely falsified [86], and although consumers are led to believe civet coffee is produced through the collection of civet faeces by Indonesian farmers, the reality is the mass farming of caged civets to meet the demand of the global market [87]. Civet coffee's global market is currently increasing and is expected to reach US $11.75 billion by 2030 [77].…”
Section: Civet Coffeementioning
confidence: 99%
“…While the civet coffee phenomenon originates in Indonesia, its global market growth has seen the emergence of civet coffee farms across the species' distribution, including Indonesia, Singapore, Vietnam, and India [77]. The capture of wild civets can take the form of caged capture or snaring, and so civets can often be inflicted with injuries through the process of wild harvesting [86]. Although civet coffee farming is permitted by law in several range countries, research has shown that civet coffee farms are often over the legal stocking density [86] or include endangered civet species [88,89].…”
Section: Civet Coffee and Civet Welfarementioning
confidence: 99%
See 3 more Smart Citations